The socialization of student’s communication with teachers at Agia Sophia High School Medan - Eva Margareth Sarah; Niscaya Hia; Roberto Roy Purba (Peneliti Teknologi Teknik Indonesia, 2022)
The current development and importance of communication can be demonstrated by the expansion of sophisticated and relatively sophisticated communication devices at all levels of society. Humans can respond to each other in everyday life at the home, workplace, or in the community by communicating. Good communication, especially between teachers and students at school, can lead to success. The community service team collaborated with Agia Sophia Medan, one of Terrain City’s private high schools. The Agia Sophiahigh school medan was a platform for organizing ideas and contributions to contribute to the community, particularly the agia high school student medan through socializing activities. Lectures, tutorials, and discussions were the methods for socialization. After implementing the program, the teacher was given a questionnaire to see if there were any changes for the better in the students' attitudes after socializing communication norms.